2016
DOI: 10.1371/journal.pone.0148286
|View full text |Cite
|
Sign up to set email alerts
|

Chromoendoscopy with a Standard-Resolution Colonoscope for Evaluation of Rectal Aberrant Crypt Foci

Abstract: Colorectal cancer (CRC) is the second most common cause of death worldwide. According to the theory by Vogelstein, colorectal carcinogenesis involves a series of successive changes in the normal colonic mucosa, starting with excessive proliferation and focal disorders of intestinal crypts, followed by adenoma and its subsequent malignant transformation. The first identifiable changes in CRC carcinogenesis are aberrant crypt foci (ACF). ACF are invisible during routine colonoscopy yet are well identifiable in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…After 45 years, the number of ACF rapidly increases to reach the plateau phase at ~60 years of age, and slowly decreases thereafter. Other studies have reported similar incidence rates of ACF in these age brackets (15,16). It is essential to identify and remove these early lesions for an adequate CRC prevention strategy (17).…”
Section: Introductionsupporting
confidence: 65%
“…After 45 years, the number of ACF rapidly increases to reach the plateau phase at ~60 years of age, and slowly decreases thereafter. Other studies have reported similar incidence rates of ACF in these age brackets (15,16). It is essential to identify and remove these early lesions for an adequate CRC prevention strategy (17).…”
Section: Introductionsupporting
confidence: 65%
“…Neoplasia progresses over time. ACF are the most common, endoscopy-identifiable colonic epithelial neoplasms [ 20 ]. In our study, ACF occurred sporadically since the age of about 40 years; predominantly single foci were found [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACF are the most common, endoscopy-identifiable colonic epithelial neoplasms [ 20 ]. In our study, ACF occurred sporadically since the age of about 40 years; predominantly single foci were found [ 20 ]. Since the age of 45 years, the number of ACF rapidly increased to reach the plateau phase about the age of 60 years and subsequently slowly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the diagnostic yield of endoscopy when using histology as gold standard to be between 60% and 68% (11,31). In our cohort, 80% of the lesions identified by endoscopy as potential ACF were corroborated by their histology, thus indicating that high-definition CE was a suitable technique for detecting these subtle lesions (32).…”
Section: Discussionmentioning
confidence: 62%